Typology of Pretty's Participation in The Development of Ecology-Based Tourism Destinations - Muharis Muharis; Muhamad Alam Setiawan (CV. ULIL ALBAB CORP, 2025)
The development of ecotourism-based tourist destinations has become an increasingly popular approach in Indonesia for environmental conservation and enhancing the well-being of local communities. This study aims to analyse the level of local community participation in the development of ecotourism destinations using Pretty's typology of participation and to identify the factors influencing it. The methodology employed is qualitative descriptive data analysis, with data obtained from a literature review encompassing international and national journals, documents, books, and other information sources. The research findings indicate that community participation in ecotourism development ranges from passive participation to self-mobilization, with interactive participation being the most ideal form to ensure social, economic, and environmental sustainability. Interactive and functional participation, where the community actively engages in decision-making and implementation, have been shown to enhance a sense of ownership and responsibility towards the environment and create sustainable economic opportunities. Additionally, the case study in Bale Mangrove Dusun Poton Bako demonstrates that management by the local community can achieve the independence of the tourist destination. By understanding the dynamics of community participation, more effective strategies can be formulated to optimize the role of the community in the development of ecotourism. This will create a synergy between environmental conservation and the improvement of community welfare.